Synthesis, Characterization and X-Ray Diffraction Studies of Co(II), Ni(II) and Pd(II) Complexes of Schiff Base Derived from 3-Hydroxy benzaldehyde and 3-Hydroxy-2-naphthoic hydrazide - PAWANOJI, A.A.; MEHTA, B.H. (Asian Journal of Chemistry, 2010)
Schiff base ligand (L) was synthesized using 3-hydroxy benzaldehyde and 3-hydroxy-2-naphthoic hydrazide. The complexes of cobalt(II), nickel(II) and palladium(II) with this bidentate ligand were synthesized having metal:ligand stoichiometry 1:2 or 1:1. The ligand and respective complexes were characterized for their analytical parameters and various spectral features. The structures of these complexes were proposed on the basis of elemental analysis, molar conductivity, IR, 1H NMR, thermogravimetric method, electron absorption spectra and X-ray diffraction. The IR spectral data suggest that the ligand (L) behaves as a monobasic bidentate ligand with nitrogen and oxygen donor atoms towards metal ions. Magnetic susceptibility measurement indicates paramagnetic behaviour for Co(II), Ni(II) complexes and diamagnetic behaviour for Pd(II) complex. X-ray diffraction studies suggest orthorhombic crystal system for all the complexes.